Unbalance mitigation strategy and power quality improvement in microgrids using a state feedback controller and voltage profile improvement with an electric spring - Sanaei, Mehdi; Akbari, Hamidreza; Beheshtipour, Zohreh; Mousavi, Somayeh (Frontiers in Energy Research, 2025)
One of the most important issues with microgrids is the optimal allocation of power between distributed generation sources and the mains, so that DG sources connected to the microgrid by electronic-power interfaces must be able to share the needs for their local loads and common loads properly. This paper will present a control method using a mode feedback controller to control the switching of interface converters and compensate unbalanced and nonlinear loads. This controller will use a linear grade 2 regulator to generate a suitable interest margin and will optimally distribute the load between distributed generation sources. The proposed compensator can balance the load, compensate the harmony, and control the reactive power and provides the actual power required by the network. Additionally, unfavorable voltage profiles and voltage fluctuations due to load change and variable generation of renewable sources are the problems of microgrids. Recently, a device called an electric spring has been introduced to respond to the load dynamics and improve the voltage profile in the microgrid. This paper also proposes a comprehensive strategy to use electric springs in order to improve the voltage profile.